Uncovering the Characteristics of Low Birth Weight Babies in Agricultural Areas - Wahyuningsih, Sri; Hayati, Nurul; Musviro, Musviro; Ersyad, Triesnawati (NurseLine Journal, 2023)
Background All mothers, including in agricultural areas, expect normal delivery Babies born are expected to also be normal. Purpose Uncovering the causes of low-birth-weight babies in agricultural areas. Methods Descriptive research to explain existing facts The population is low birth weight babies aged 0-28 days who are treated in the Neonatal room of RSUD dr. Haryoto Lumajang. Retrieval through 50% of cases from 2020-2022 Results are analyzed using frequency distributions displayed in graphical. Results The characteristics of low-birth-weight babies in the farming community at RSUD dr. Haryoto Lumajang that was found includes gestational age, type of delivery, complicating maternal labor, complicating baby birth, the birth of the child to or parity, and also the value of the baby's Apgar Score. Conclusion Maximum treatment that is appropriate for the cause of low-birth-weight babies can prevent or minimize abnormal growth and development.